Human Hepatic CD56bright NK Cells Display a Tissue-Resident Transcriptional Profile and Enhanced Ability to Kill Allogenic CD8+ T Cells - Jameson, Gráinne; Harmon, Cathal; Santiago, Rhyla Mae; Houlihan, Diarmaid D.; Gallagher, Tom K.; Lynch, Lydia; Robinson, Mark W.; O’Farrelly, Cliona (Frontiers in Immunology, 2022)
Liver-resident CD56brightCD16- natural killer (NK) cells are enriched in the human liver and are phenotypically distinct from their blood counterparts. Although these cells are capable of rapid cytotoxic effector activity, their functional role remains unclear. We hypothesise that they may contribute to immune tolerance in the liver during transplantation. RNA sequencing was carried out on FACS sorted NK cell subpopulations from liver perfusates (n=5) and healthy blood controls (n=5). Liver-resident CD56brightCD16+/- NK cells upregulate genes associated with tissue residency. They also upregulate expression of CD160 and LY9, both of which encode immune receptors capable of activating NK cells. Co-expression of CD160 and Ly9 on liver-resident NK cells was validated using flow cytometry. Hepatic NK cell cytotoxicity against allogenic T cells was tested using an in vitro co-culture system of liver perfusate-derived NK cells and blood T cells (n=10-13). In co-culture experiments, hepatic NK cells but not blood NK cells induced significant allogenic T cell death (p= 0.0306). Allogenic CD8+ T cells were more susceptible to hepatic NK cytotoxicity than CD4+ T cells (p<0.0001). Stimulation of hepatic CD56bright NK cells with an anti-CD160 agonist mAb enhanced this cytotoxic response (p=0.0382). Our results highlight an important role for donor liver NK cells in regulating allogenic CD8+ T cell activation, which may be important in controlling recipient CD8+ T cell-mediated rejection post liver-transplant.